Analisis Kesadaran Pasien Akan Pentingnya Penggunaan Masker Terhadap Penyebaran Penyakit Tuberculosis Di Area Poliklinik Rumah Sakit Muhammadiyah Bandung - Hidayat, Choirul Salam; Ariani, Nurul Dwi (Barongko: Jurnal Ilmu Kesehatan, 2024)
This study aims to provide insight to TB patients in the polyclinic area of the Bandung Muhammadiyah Hospital about the factors that influence TB patients' awareness and behavior towards mask use, as well as emphasizing the importance of a holistic approach to TB management to reduce its spread and improve public health. The method used in this study is a quantitative method with a descriptive approach, while the data collection technique is by means of questionnaires and interviews with TB patients visiting the polyclinic. In this study, researchers found problems in terms of using masks to prevent the spread of TB disease such as: (1) Lack of patient habits using masks (2) Patient ignorance of the use of masks (3) Lack of education from doctors / nurses on the use of masks to patients. Based on the problems that occur above, the researcher tries to provide the following suggestions: (1) Hospitals must provide education to patients to use masks such as making campaign events in the polyclinic area so that patients know the importance of using masks for themselves (2) Make banners or make video documentaries about how crucial the use of masks is to prevent disease transmission (3) Doctors / nurses must always tell patients to always use masks, especially in the polyclinic area and always urge TB patients if they do not use masks, they will be vulnerable to transmitting TB disease.